Critique as a Disposition - Williams, John (Springer Nature, 2017)
The appeal of perceiving critique as a disposition lies in its essentiality of action; the ability to critique is an important prerequisite, but when an individual is disposed to act as a result of cognitive critique, then the outcome has effect. This notion aligns well with concepts of technological literacy as the goal of design and technology education. It has been argued that this form of literacy must have a capability element to it, and if the critique element of this capability is dispositional, then technological literate students will be active in their relationships with technology.